Pre-transplant heavy smoking is associated with reduced survival after heart transplantation due to infection and malignancy - Heil, Karsten M.; Rivinius, Rasmus; Helmschrott, Matthias; Rahm, Ann-Kathrin; Ehlermann, Philipp; Frey, Norbert; Darche, Fabrice Fernand (Journal of Clinical Medicine, 2025)
Background: Tobacco smoking is a known risk factor for adverse cardiovascular events. Many patients after heart transplantation (HTX) have a history o...
Gesehen am 14.01.2026